A wide-frequency range dielectric tuning of BaTiO3 by embedding metal nanocrystals. Issue 24 (19th April 2021) - Xiong, Zhengwei; Liu, Qian; Tang, Jinlong; Fang, Leiming; Zhang, Xiaoqiang; Li, Jun; Fu, Yajun; Wang, Jin; Gao, Zhipeng; Shi, Deli
Abstract : An ideal model was provided for explaining the effects of the interaction between grains and grain boundaries on their dielectric and rectification characteristics. Abstract : Fe nanocrystals (NCs) were embedded into the epitaxial BaTiO3 (BTO) matrix. According to optimized growth processes, a novel nanocomposite system was constructed, which consisted a well epitaxial BTO layer and three-dimensional Fe NCs. Based on this, the different dielectric response in the regions of low temperature-high frequency and low frequency-high temperature were revealed by the contribution of hopping and interfacial polarizations, respectively. With the increased amount of Fe NCs, the obvious enhancement in the low-frequency conductivity, middle frequency capacitance, and high-frequency inductive effect was found. The embedded metal NCs play an important role in tuning the dielectric behaviors and AC conductivity of oxide dielectrics. This significant rectification effect in wide-frequency ranges opens up a new direction for designing embedded nano-capacitors.